Beyond a Ribosomal RNA Methyltransferase, the Wider Role of MraW in DNA Methylation, Motility and Colonization in Escherichia coli O157:H7 - Xu, Xuefang; Zhang, Heng; Huang, Ying; Zhang, Yuan; Wu, Changde; Gao, Pengya; Teng, Zhongqiu; Luo, Xuelian; Peng, Xiaojing; Wang, Xiaoyuan; Wang, Dai; Pu, Ji; et al. (Frontiers in Microbiology, 2019)
Abstract MraW is a 16S rRNA methyltransferase and plays a role in the fine-tuning of the ribosomal decoding center. It was recently found to contribute to the virulence of Staphylococcus aureus. In this study, we examined the function of MraW in Escherichia coli O157:H7 and found that deletion of mraW led to decreased motility, flagellar production and DNA methylation. Whole-genome bisulfite sequencing showed genome wide decrease of methylation of 336 genes and 219 promoters in the mraW mutant including flagellar genes. The methylation level of flagellar genes were confirmed by bisulfite PCR sequencing. Quantitative reverse transcription PCR results indicated that the transcription of these genes was also affected. MraW was furtherly observed to directly bind to the four flagellar gene sequences by electrophoretic mobility shift assay (EMSA). A common flexible motif in differentially methylated regions of promoters and coding regions of the four flagellar genes was identified. Reduced methylation was correlated with altered expression of 21 of the 24 genes tested. DNA methylation activity of MraW was confirmed by DNA methyltransferase activity assay in vitro and repressed by DNA methylation inhibitor 5-aza-2’-deoxycytidine (5-aza). In addition, the mraW mutant colonized poorer than wild type in mice. We also found that the expression of mraZ in the mraW mutant was increased confirming the antagonistic effect of mraW on mraZ. In conclusion, mraW was found to be a DNA methylase and have a wide-ranging effect on E. coli O157:H7 including motility and virulence in vivo via genome wide methylation and mraZ antagonism.